Entre mito e alegoria: a construção simbólica dos Sertões na ficção de Ariano Suassuna - Oliveira, Sebastião de (2010)
The pair myth/allegory are two important elements in the symbolical construction of the countries (sertões) in Ariano Suasassuna‘s work. The study of the relationship between metaphorical tropes and the countries image presented by the metaphors will make possible to understand the multiple country‘s faces through the temporal-space door opened by the tropes. In Northrop Fry (2004), Heinrich Lausberg (1993) and Paul Ricoeur (2000), we have a theoretical baseline to the realization of this work, because basically the distinctive notions necessary to the meaning operations among symbol, myth and allegory as well the transposition from literal meaning to figurative meaning are clearly defined in these author‘s view, especially on the time-space perspective mentioned above. This work seeks to study the structure of the countries (sertões) showed in Ariano Suassuna‘s work. So, our interest is to examine in what kind of register is operated the symbolical construction of Ariano Suassuna‘s countries based on the cited tropes.